Trace metals, peroxidase activity, PAHs contents and ecophysiological changes in Quercus ilex leaves in the urban area of Caserta (Italy). (Journal of environmental management, 2012)
Trace metals and polycyclic aromatic hydrocarbons, severely affecting human, animal and plants health, highly contribute to the air pollution in urban areas mainly due to car traffic. In this study the air biomonitoring of the city of Caserta (South Italy) has been performed by using Quercus ilex L., a widespread ornamental plant in parks, gardens and avenues. The plant leaves from different sites within the urban area were collected and used to determine the concentrations of V, Cd, Cr, Pb, Ni, Cu, and PAHs as well as the free amino acid content and peroxidase enzyme activity as indices of the leaf physiological conditions. All the tested trace metals showed concentrations higher than the control site. Lead was positively correlated to Cd and Cr and showed, also, a positive trend with Ni and Cu that, in their turn, were highly correlated between them. Positive and significant correlations were evidenced between total PAHs and carcinogenic PAHs and negative correlations between those and all trace metals assayed except V. Cu and Cd contents evidence negative correlations with peroxidase activity, and the free amino acid contents. The PAHs, in particular Carc-PAHs, were negatively correlated to the tested heavy metals. POD was positively correlated only with V and negatively correlated with Cu and Cd.

Microbial activities in soils of a Mediterranean ecosystem in different successional stages - Fioretto, a; Papa, S.; Pellegrino, a; Ferrigno, a (Soil Biology and Biochemistry, 2009)
This study reports a comparative analysis of soil enzyme activities (b-glucosidase, protease, urease, arylsulphatase, phosphatase and ﬂuorescein diacetate hydrolase), ATP, total N and organic matter contents in three vegetal successional stages (meadow, low shrubland and high maquis) of a Mediterranean ecosystem in the Natural Reserve of Castel Volturno (Campania, Italy). Because water availability is a major limiting factor of soil microbial activity in Mediterranean ecosystems, the analysis was performed in late spring (May), after the rainy period, and in early autumn (October), after the long dry summer. A signiﬁcant decrease in protease, arylsulphatase, urease and b-glucosidase activities was observed in meadow soil in the autumn sampling, probably due to the prolonged summer drought. Combining the values measured in the two sampling dates, the high maquis tended to have higher levels of enzymes activities than shrubland and meadow. Notably, high maquis had signiﬁcantly higher phosphatase and arylsulphatase activities than shrubland and meadow and, in addition, a higher ATP content compared to meadow. Drastic changes were observed in EA/ATP ratios between the sampling periods in the meadow and shrubland, suggesting changes in the efﬁciency of microbial community more likely linked to climatic ﬂuctuations than to the successional stage. The more stable EA/ATP ratio in the maquis probably reﬂects a constant contribution of microbial biomass to enzyme secretion. In conclusion, our results point to an increase in soil microbial activity accompanying the succession from meadow to high maquis that probably reﬂects a parallel increase in soil functions. Nevertheless, spatial heterogeneity and, more important, temporal variations in soil activities often may obscure differences related to the plant cover type.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: ATP; High maquis; Meadow; Mediterranean ecosystem; Shrubland; Soil enzyme activities; Successional stages

Microbial activity and quality changes during decomposition of Quercus ilex leaf litter in three Mediterranean woods (Applied Soil Ecology, 2008)
Changes in enzyme activities during litter decomposition provide diagnostic information on the dynamics of decay and functional microbial succession. Here we report a comparative study of enzyme activities involved in the breakdown of major plant components and of other key parameters (microbial respiration, fungal biomass, N, lignin and cellulose contents) in homogeneous leaf litter of Quercus ilex L. incubated in three evergreen oak woods in Southern Italy (Campania), differing for chemical and physical soil characteristics and microclimatic conditions. The results showed that the litter mass loss rates were similar in the three wood sites. Independently of the incubation sites, cellulase, xylanase and peroxydase activities showed seasonal variations with maximum and minimum levels in wet and dry periods, respectively, and this pattern closely matched microbial respiration. Activities of a- and b-amylase, instead, were high at the beginning of incubation and quickly decreased with decomposition progress because their substrate was rapidly depleted. Laccase activity, in contrast, was low at the beginning of incubation but after 6 months it increased signiﬁcantly. The increase of laccase activity was correlated to an increase in fungal biomass, probably reﬂecting a major shift in the litter microbial community. As concerns quality changes, N and lignin content did not signiﬁcantly change during decay. The cellulosic component started being degraded after about 6 months in the litter incubated in two of the three wood sites and from the start of decomposition in the third site. Apart from minor differences in the levels of certain enzyme activities, the data showed that the functional microbial succession involved in the decomposition of Q. ilex leaf litter did not change appreciably in response to differences in soil and microclimatic conditions in the incubation sites.

Decomposition dynamics of Myrtus communis and Quercus ilex leaf litter: Mass loss, microbial activity and quality change (Applied Soil Ecology, 2007)
The patterns of microbial respiration and enzyme activity (cellulase, xylanase, laccase and peroxidase) in the leaf litter of two evergreen sclerophyll species, Myrtus communis and Quercus ilex, were compared during decay in a low shrubland and in a coppice wood in a Natural Reserve in the Mediterranean area. The two litter types had similar initial amounts of lignin, cellulose and acid-detergentsoluble substances, but the litter from M. communis had a lower N content and higher C/N ratio. In spite of this, the decomposition rate of M. communis litter was higher than for Q. ilex. Whilst no seasonal variation was observed in the rate of organic matter degradation, respiration and extractable cellulase and xylanase activities showed seasonal variation in both litter types with the highest values in winter–early spring and the lowest in summer, and showed positive correlations with water content. Peroxidase activity exhibited a seasonal pattern and was higher in Q. ilex than in M. communis, while laccase activity was higher in M. communis and increased with fungal biomass as degradation progressed. Nevertheless, no relationship was found between laccase and peroxidase activity and lignin degradation. The results obtained indicate that the seasonal alternation of moist and dry periods is the major factor inﬂuencing soil biological activity in the Mediterranean area. The occurrence of pronounced seasonal variation in litter enzyme activity prevents the determination of possible correlations with litter mass loss.